Anatomy of treaty-based regimes - Zapatero, Pablo (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Treaty-based regimes, as the principal institutionalized form of inter-state cooperation, constitute the primary sources of authority in international law, yet they fundamentally reflect the paradigm of intergovernmental functionalism. Examination of their secondary rules, together with the observation of functionalist practice, shows that special regimes are inherently constrained by internal (or contextual) primacies—limitations that persist despite attempts to incorporate broader public rationalities. Whether operating individually or collectively, they remain structurally ill-suited to effectively ensure the consistency of international rules and decisions. Far from marginal, this issue has constitutional significance, as treaty-based regimes constitute the principal form of international authority today.
Keywords: treaty-based regimes; international authority; global public goods and values; intergovernmentalism; functionalism; secondary rules